THE EVOLUTION AND TREATMENT IN HAEMOLYTIC-URAEMIC SYNDROME IN CHILDREN - Maria Daniela Tănăsescu; Dorin Dragoș; Adrian Georgescu (Amaltea Medical Publishing House, 2008)
The present paper reviews the treatment and the outcome of a sample of 48 children with haemolytic-uraemic syndrome (HUS) hospitalized during 1972-2003 in the paediatric clinics Alfred Rusescu, Fundeni and Grigore Alexandrescu. The therapeutic approach includes several stages: 1. conservative and supportive treatment; 2. dialysis; 3. aetiopathogenic treatment; 4. the treatment of complications; 5. the treatment of recurrences; In some cases a rapid substitution of the renal function was required. A rapidly deteriorating renal function should be regarded as a major emergency, and the dialysis should be initiated with no further delay. When needed, the substitution of the renal function clearly improves the outcome in HUS children. The earlier the diagnosis of HUS is established and the sooner the therapy is initiated, the better are the outcome and the prognosis. The outcome in the typical form of HUS was generally toward restitutio ad integrum, with a favourable prognosis and no recurrence. In the atypical form of HUS, the recovery is usually flawed with sequelae: 1. persistent proteinuria; 2. high blood pressure; 3. chronic renal failure